Experimental and density functional theory investigations on the structural and electronic properties of acyclovir and theophylline hydrate molecules - Wang, Suh Miin (2021)
Acyclovir (ACV) and theophylline (TP) drug compounds have gain high attentions in the study of polymorphism to improve their therapeutic performances, since both of them are the potent treatment solutions for global burden diseases of Herpes Simplex Virus (HZV), Varicella Zoster Virus (VZV), asthma, and chronic obstructive pulmonary disease (COPD). Surveys show that there is limited information about the Density Functional Theory (DFT) computational works on both compounds. So that, the work undertaken in this research study concerns the geometry structures and electronic properties investigations on the hydrated polymorphic forms of ACV (i.e. hydrated ACVI, ACV-II, and ACV-III) and TP (i.e. anhydrous TP-I and monohydrated TP-II) active pharmaceutical ingredients (APIs) drug compounds. First, the polymorphism behaviors of ACV and TP compounds were observed from the crystal formation of ACV-I, TP-I, and TP-II via crystallization technique. The details of the crystal molecular structures were characterized through the single crystal X-ray diffraction experiment and acted as the main input sources for Density Functional Theory (DFT) computational calculations. Besides, Fourier transform infrared (FT-IR) and Ultraviolet-visible (UV-Vis) spectroscopy techniques were conducted and used as the guiding references for DFT computational data. In this project, DFT/B3LYP/6-31G** and DFT/B3LYP/6- 311G** level of calculations were chosen for ACV-I, ACV-II, and ACV-III molecular system, whereas DFT/B3LYP/6-31G and DFT/B3LYP/6-31G** level of theories were implemented for TP-I and TP-II molecular system. Geometry optimization calculations were performed to obtain the equilibrium structures of ACV-I, ACV-II, ACV-III, TP-I, and TP-II molecular system. Besides, single point calculations were carried out to determine the electronic properties (i.e. total energies, highest occupied molecular orbital-lowest unoccupied molecular orbital (HOMO-LUMO) energies, molecular electrostatic potential (MEP), natural bond orbital (NBO), and non-liner optical (NLO)) and FT-IR vibrational spectral of ACV-I, ACV-II, ACV-III, TP-I, and TP-II molecular system. From the computational data, ACV-I molecular system with computed total energies of -70358.746 eV (6-31G**) and -70376.691 eV (6-311G**), was dominated to be the most stable molecular structure among ACV-II and ACV-III molecular system. For TP-II molecular system, with total energies of -19517.293 eV (6-31G) and -19524.267 eV (6-31G**), it was found to be more stable than the TP-I molecular system. Besides, the computed HOMO-LUMO energy gaps of ACV-I and ACV-II using DFT/B3LYP/6-31G** and DFT/B3LYP/6-311G** methods were situated in the ranges of 4.889 eV to 5.012 eV, while for ACV-III molecular system were calculated to have ranges of 4.049 eV to 4.545 eV. Both of the computed HOMO-LUMO energy gaps of TP-I and TP-II using DFT/B3LYP/6-31G and DFT/B3LYP/6-31G** methods elucidated closer results within each other (i.e. 5.002 eV to 5.147 eV). For the NLO properties analysis, ACV-II molecular system with dipole moments of 14.822/14.600 Debye (6-31G**/6-311G**) and first hyperpolarizability of 6.690 x 10-29/ 6.837 x 10-29 e.s.u (6-31G**/6-311G**), showed better NLO characteristic than ACV-I and ACV-III molecular system. For TP-I molecular system, the calculated dipole moments and first hyperpolarizability were reported to be 3.642/3.481 Debye (6-31G/6-31G**) and 7.598 x 10-30/7.378 x 10-30 e.s.u (6-31G/6-31G**), whereas for TP-II molecular system were 2.562/2.332 Debye (6-31G/6-31G**) and 10.750 x 10-30/10.130 x 10-30 e.s.u (6- 31G/6-31G**). All the findings of the calculated FT-IR vibrational frequencies of ACV-I, ACV-II, ACV-III, TP-I, and TP-II molecular system met good agreement with the experimental and literature data. In additions, size effect studies were conducted on TP-I and TP-II molecular system. An increase in the molecular system size of TP has shown an impact on the accuracy of the computational data. Furthermore, rotational barrier studies were carried out on ACV-I, ACV-II, and ACV-III molecular system through the Potential Energy Surface (PES) scanning method to figure out the possible conformations of ACV molecules. The computed data elucidated that the extension of the bond distance C-O in the ACV molecule will result in unstable conformers. Noted that all the DFT computational findings in both ACV and TP polymorphic forms found satisfactory agreement with experimental data. In particular, the DFT results obtained in this work can be served as a complement for real system work and act as guideline resources for researchers in the future.